A Review on the Importance of Pharmacy Practice in Day-To-Day Life - Ganguly, Debgopal; Ghosh, Soumyadip; Banerjee, Madhumita; Chakraborty, Pubali; karar, Pradip Kumar (Asian Journal of Pharmaceutical Research and Development, 2022)
Pharmacist is also known as chemist or druggist as health care professionals who practice in pharmacy deal with the field of medicine and provide proper medication and are also involved in the field of preparation, standardization, formulation, quality checking, inspection, compounding, and dispensing of the different types of drug of several dosage forms in such a way the medication preferable for a simplified route of administration in the treatment of local as well as chronic diseases. Pharmacists are healthcare professionals who worked in a wide variety of health care systems such as in the pharmaceutical industry for innovation (R&D), formulation, manufacturing, processing, quality checking, and maintaining proper safety and toxicity parameters. Pharmacists are involved in patient education and worked in collaboration with physicians and other health care professionals for the prevention of disease and the treatment of patients. This article discusses a review on the importance of the pharmacy practice in different fields and fundamental characteristics of involvement in day-to-day life and plays a to assure patient benefits from rational evidence-based medication and improvement of patient care. There is a need for a system of assuring the integrity of the medicine supply chain to assure the value of medicines used very important role during the Covid19 pandemic.